Sovereign soldiers how the U.S. military transformed the global economy after World War II - Madsen, Grant (University of Pennsylvania Press, 2018)
In Sovereign Soldiers, Grant Madsen tells the story of how this cast of characters assumed an unfamiliar and often untold policymaking role. Seeking to avoid the harsh punishments meted out after World War I, military leaders believed they had to rebuild and rehabilitate their former enemies; if they failed they might cause an even deadlier World War III. Although they knew economic recovery would be critical in their effort, none was schooled in economics. Beyond their hopes, they managed to rebuild not only their former enemies but the entire western economy during the early Cold War.